EFFECT OF JOGGING PROGRAMME ON VISCERAL FAT OF ALMAJIRAI IN TSANGAYA IN GUSAU METROPOLIS, NIGERIA (Isagoge - Journal of Humanities and Social Sciences, 2021)
This study therefore assessed the effect of jogging programme on visceral fat of Almajirai in Tsangaya in Gusau Metropolis, Nigeria. For the purpose of this study, a 1x2 x3 factorial research design was used. The population are Almajirai who are gardi in Gusau Metropolis within the ages of 13-15 years, stratified sampling and simple random sampling technique were used to select 48 Gardi Almajirai in Gusau metropolis who volunteered to participate in the study. Hand-held Bioelectrical Impedance Analysis device was used to assess visceral fat. All of these Girdi Almajirai were found to have met the inclusion criteria and were all assigned to the jogging programme and the baseline values were used as the control. All exercise sessions were preceded by 10 minutes warm-up; the programme lasted between 30 and 45 minutes, which ended with a cool down session. All exercise sessions were conducted between 5.30p.m - 6.00p.m on alternate days every Monday, Wednesday and Friday of the consecutive weeks. Training intensity was maintained between 50-65% of estimated HR max  for 4 weeks and which was increased progressively from 60-70% from the 5 to 8 weeks of training. The data collected were statistically analyzed using repeated measured ANOVA and scheffe post hoc test was used to locate where significant effect lies at level of 0.05. The result of the study revealed that jogging had significant effect on visceral fat p=0.001. It was recommended that Adolescent almajirai should participate every day in 45 minutes or more of moderate to vigorous physical activity that is enjoyable and developmentally appropriate.
Keywords: Jogging; Programme; Visceral fat; Almajirai; Tsangaya